Standardization and the Production of Justice in Summary Criminal Courts: A Post-Human Analysis. (December 2019) - Welsh, Lucy; Howard, Matt
Since the 1980s, successive governments have become increasingly distrustful of professional judgment in those services which remain funded by the state, including the criminal justice system. Against this background, governments sought to increase efficiency in summary criminal courts. One way that this seems to have occurred is via the use of standardized forms in case progression. During 2013, Welsh conducted empirical research in which the reliance placed on standardized case management forms became apparent. We argue, drawing on post-humanist vocabularies to inform our analytic framework, that such documents may have shifted the temporality of summary criminal justice, which has the (perhaps unintended) consequence of (further) marginalizing defendant participation and limiting the types of legal issue that are litigated. These documents and processes, therefore, participate in the development of a particularized, and temporally situated, form of 'justice'.